THE (RE)WRITING OF THE FEMALE FIGURE AND IRISH-AMERICAN HISTORY IN NUALA O’CONNOR’S MISS EMILY - Franco Batista, Camila (Revista Alere, 2017)
This article analyses the (re)writing of the female figure in the historical novel Miss Emily (2015), by the Irish writer Nuala O’Connor (b. 1970). It considers how the historical figure of the North-American poet Emily Dickinson (1830-1886) is fictionally recreated to explore issues, such as sexuality, sexual violence, and gender roles. This work also aims to investigate the rewriting of Irish-American relations in the novel by means of the fictional Irish maid Ada Concannon and the issue of migration and racial discrimination. This article focuses on the way the female figure, historical or not, is reinserted in contemporary historical fiction by women to provide visibility and to restore the female figure as a protagonist of history.